Assessing malaria control in the kassena-nankana district of northern Ghana through repeated surveys using the RBM tools - Owusu-Agyei, S.; Awini, E.; Anto, F.; Mensah-Afful, T.; Adjuik, M.; Hodgson, A.; Afari, E.A.; Binka, F. (My University, 2007)
The goal of Roll Back Malaria (RBM) is to reduce malaria morbidity and mortality by 50% by the year 2010, and still further thereafter until the disease becomes no more a threat to public health. To contribute to the monitoring and evaluation process of this goal, two surveys were carried out in 2000 and 2003 in households and health facilities in the Kassena-Nankana district, northern Ghana using the RBM-WHO/AFRO monitoring and evaluation tools for malaria control activities. METHODS: Data were collected from mothers/caretakers on signs/symptoms of the most recent malaria attack for their under five year old children; the management actions that they took and their perception of health services provided at the health facilities, bednet use, antenatal attendance and place of delivery for the most recent pregnancy, malaria prophylaxis during their last pregnancy. Community health workers and herbalist/traditional healers were also interviewed about the types of health services they provide to community members. RESULTS: The results revealed a significant improvement in knowledge among mothers/caretakers over the three-year period; this affected caretakers' initial management of illnesses of their young children. The management in terms of the type and dosage of drugs used also improved significantly (p < 0.0001) over the period. Reported insecticide-treated bed net use among children under-five years and pregnant women significantly increased between 2000 and 2003 (p < 0.0001). Health professionals had improved on adoption of their quality of care roles. The intensification of malaria control activities and awareness creation in this district over a three year period had started demonstrating positive results towards reducing malaria disease burden. CONCLUSION: Periodic performance assessments through surveys as described and prompt feedback of results to stakeholders in the locality serves as a catalyst to improving malaria control in malaria-endemic countries.